Aplikasi Sistem Parkir dengan Automatisasi Pembiayaan Berbasis RFID (Radio Frequency Identification) - Velayati Habsyah; Yuli Christyono; Imam Santoso (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
RFID ( Radio of Frequency Identification ) is technology base on the this wave radio. Technology able to identify without needed direct contact. RFID developed by in the place of barcode technology. Implementation RFID is among other things used for the approximation of last stream - pass by quickly at turnpike, system of applying of application RFID in that library area, and what is more there are also research RFID used for the university student card, library card and polyclinic card, application of transaction of voucher and fingerprint and breach-block electronic at smart home. In this final project, the writer do the simulation program with automatic park system by using RFID (Radio Frequency Identification).It is expected that using this tool, to help in arranging the park field that using auto identification technology which does not need direct contact in the usage. In this final project, besides making the parking transaction easier, RFID also used as the substitution of money during the transaction. This technology also offers safety. The using of RFID in parking managing gives significant advantages if it is compared with Barcode technology. The design starts with RFID to data input in database and will be used turn on LED like supplementary gate park. Examining process the park transaction include enter transaction park and exit transaction park. In the testing stage, the system can work well and it can be shown by RFID reading not a wrong. The output of this system is identified by LED (Light Emitting Diode) supplementary gate park which creates green color if the system is success and red color if the system cannot be continued. Keyword : Barcode, Identification, LED (Light Emitting Diode) ,RFID (Radio Frequency Identification), park system , tag RFID.